PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA AUDIT MUTU INTERNAL ISO 9001:2008 DI UNIVERSITAS BUNDA MULIA, JAKARTA - Yustinus Yuniarto (Business Management Journal, 2016)
This study discusses about "Effect of Competence and Auditor independency on the Quality Audit on Internal Quality Audit System ISO 9001: 2008 at the University of Bunda Mulia". The purpose of this study to determine how much influence the competence and independence of the quality audit on internal quality audit system is ISO 9001 so that it can be made in the audit strategy and the determination of the auditor. In this research produced the conclusion that the value of the regression coefficient competence (X1) of 0.022 and has significant value <0.05 proves that competence significant effect on audit quality. Then the value of the independence of the regression coefficient (X2) is 0,747dan have significant value> 0.05 proving that independence had no significant effect on audit quality.Calculated F value of 4.767> F table at 4.11 and significant value of 0.032 <alpha value of 0.05. This means there is a simultaneous effect between competence and independence to audit quality.Keywords: internal quality audits, internal auditor, competence, independence, quality audits, ISO 9001: 2008